O corpo à luz da ontofenomenologia sartriana: sobre a integralidade corpo consciência - Pôncio, Franciele Maria (2022)
The actual thesis refers to the Sartrean notion about the body. Under this perspective, the research is not just an epistemological or descriptive study of the body, but a knowledge that comes from the subject as a whole in the world. In this context, the general objective of this study is to explain the notion of the body, starting from the explanation of the considerations that Jean-Paul Sartre establishes about Cartesian duality, for then, bring to light the notion of consciousness and body under the existential perspective. Ultimately, there is the intention of researching the body in relation to the Other, as well as what links Sartrean philosophy to psychology. With this intent, the relevance of developing a study with this theme is justified by the lack of researches in Portuguese about the subject, and its importance is evidenced by the need to bring to light the integrate manifestation of body/consciousness through this perspective, as well as the theme of the being’s ontological freedom and the unique relationship of each one as being-in-the-world. For this aim, a bibliographic research was carried out, presenting Being and Nothingness (1943) as a fundamental work. In this work , we verify that the perceived world is related to the observer, given that the intention of the consciousness that is sent to is always unique to each observer, configuring itself as a singularity of the lived experience. It is in the scenario that "subjectivity" takes on the leading role that it is entitled to, as a reflection of being as a singularity in the world.